Treatment of the Dislocated Hip in Infants With Spasticity. Issue 7 (August 2018) - Refakis, Christian A.; Baldwin, Keith D.; Spiegel, David A.; Sankar, Wudbhav N.
Abstract : Background: Although many studies have separately investigated the treatment of developmental dysplasia of the hip and spastic hip disease, little data exist regarding the treatment of infants with dislocated hips and underlying spasticity. The purpose of this study was to review our results after the surgical treatment of these infants. Methods: We retrospectively reviewed all children below 3 years of age who underwent hip reconstruction for dislocated hips in the setting of cerebral palsy or other spastic/high-tone neuromuscular disease. Medical records were reviewed for clinical data including treatment course, complications, and need for further surgery. Preoperative and postoperative radiographs were used to determine International Hip Dysplasia Institute (IHDI) grade of dislocation, acetabular index, migration percentage, and presence of avascular necrosis according to the Salter criteria. Results: Eleven patients with 15 hips met our inclusion criteria with a mean age of 20±8 (range, 6 to 34) months. Preoperatively, 12 of 15 hips (80%) were IHDI grade 4 and 3 of 15 (20%) were IHDI grade 3. Mean acetabular index was 29±8 (range, 19 to 46) degrees. Patients underwent open reduction (15 hips), adductor tenotomy (14 hips), femoral osteotomy (10 hips), and pelvic osteotomy (12 hips). At a mean follow-up of 40±16 (range, 13 to 71) months, 13 of 15 hips were IHDI grade 1 (86.7%), 1 was IHDI grade 2 (6.7%), and 1 hip was IHDI grade 3 (6.7%). The mean postoperative migration index was 7%±24% (range, −30% to 46%); the mean acetabular index was 22±8 (range, 9 to 38) degrees. No patients developed radiographically significant osteonecrosis. Complications included 2 femur fractures (13.3%) and 1 symptomatic implant that required early removal. One patient underwent further reconstructive hip surgery. Conclusions: In this series of infants with hip dislocations and underlying spasticity, open reduction±pelvic osteotomy and/or femoral osteotomy has a nearly 90% success rate in achieving and maintaining adequate hip reduction at intermediate-term follow-up. In the unique population of infants with dislocated hips and underlying spasticity, comprehensive hip reconstruction is largely successful with an acceptable rate of complications. Level of Evidence: Level IV—retrospective.